Marital Status and Motherhood:Their Impact on Women's Wage - Chivaza-Ruhana, Mirindi (Université d'Ottawa | University of Ottawa, 2013)
Many people believe that women's careers suffer after they marry or have children. My research uses the most recent Labour Force survey data available in Canada to determine if marital status and motherhood status have an impact on women's wages. My research found that wages of women who have children are 4.5% higher than women who do not have children, and when married with children, their wages are 1.5% higher than the wages of their single counterparts. Furthermore, I also found that the following variables had an effect on women's wages: the level of education, the urban versus rural areas, the number of persons in a household, Part time versus Full time employment status, the size of the firm, and the tenure of the employment position. My findings show that, contrary to popular belief, women actually make slightly more in Canada when they have children, and do not suffer any wage penalties for being married or having children. This result is quite different from what has been reported in the literature for other countries such as the United States, where women do experience wage penalties for having children. A possible interpretation is that the policies in Canada that support women and mothers in the workforce are effective in reducing wage penalties. These findings have important socio-economic policy implications.